Effect of Leaching on Particle Migration and Pore Structure of Ionic Rare Earth Ores with Different Fine Particle Contents - Yunzhang Rao; Jiazheng Wan; Shujun Tan; Zhihua Yang; Guozhu Rao; Qiang Huang; Yangjun Xie; Qiande Lai (Metals)
In in situ leaching, fine particles can be stripped and transported with the leach solution, significantly altering the particle size distribution and pore structure of each layer of the rare earth ore body. In this study, water and magnesium sulfate were used as leaching agents. Based on indoor column leaching experiments, particle gradation experiments, and pore structure tests, this study investigates and analyzes the patterns of particle migration and changes in pore structure in rare earth ores with varying fine particle contents under leaching conditions. The results indicate that during the leaching process, the degree of change in particle gradation follows the order of upper layer > middle layer > lower layer. As the depth increases, the soil becomes denser, leading to reduced permeability, a slower seepage rate of the leaching solution, and a higher fine particle content, making the effect more pronounced. During magnesium sulfate leaching, the overall trend of porosity in the rare earth ore structure initially increases and then decreases. Additionally, a higher fine particle content corresponds to higher porosity. In the early and late stages of leaching, pore size changes involve the transformation of larger pores into smaller ones, followed by the conversion of smaller pores into larger ones. Moreover, the higher the fine particle content, the greater the degree of transformation between the pore sizes.